2012
DOI: 10.1111/j.1754-9485.2012.02379.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between CT attenuation value and iodine concentration in vitro: Discrepancy between gemstone spectral imaging on single‐source dual‐energy CT and traditional polychromatic X‐ray imaging

Abstract: Owing to the better correlation coefficients between CT attenuation value and iodine concentration, GSI may be a preferred method for quantitative measurement compared with TPXI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Theoretically, a strong correlation between CT values and iodine concentration is plausible because iodine is the most important determinant of the CT values of the thyroid glands [17]. An experimental study that used polypropylene phantoms filled with different concentrations of iodine solutions [18] showed a strong correlation between CT value and actual iodine concentration. In our study, however, only a moderate linear correlation was observed between 123 I uptake at 3 h and CT values of the thyroid gland in vivo, while the iodine concentration, as evaluated by DECT, showed a better correlation with 123 I uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, a strong correlation between CT values and iodine concentration is plausible because iodine is the most important determinant of the CT values of the thyroid glands [17]. An experimental study that used polypropylene phantoms filled with different concentrations of iodine solutions [18] showed a strong correlation between CT value and actual iodine concentration. In our study, however, only a moderate linear correlation was observed between 123 I uptake at 3 h and CT values of the thyroid gland in vivo, while the iodine concentration, as evaluated by DECT, showed a better correlation with 123 I uptake.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of the CT value is to estimate the iodine content, and the accuracy of this estimation is unknown. Recently introduced as a great breakthrough in conventional CT, Gemstone spectral CT can reflect the iodine concentration directly by the monochromatic imaging [22]. Thus, our study focused on the relationship of IC and thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, iodinated contrast material is potentially a good tracer for measuring GFR, which, in this context, is equivalent to the renal clearance of the contrast material. Similarly, the multidetector CT scanner is a reliable tool for investigating renal filtration of the iodinated contrast material because of a good linear relationship between CT attenuation value and its concentration (11,12). The renal clearance of the contrast material, by definition, can be determined by dividing the amount of the contrast material filtration by its plasma concentration.…”
Section: Discussionmentioning
confidence: 99%